Capital Market law of Malaysia - Shanti Geoffrey (LexisNexixs, 2010)
This book sets out a broad range of areas that are critical to how the capital markets function. It covers the regulation of exchanges, including the governance framework of the exchange post demutualisation. In the area of licensing, it outlines the single licensing framework that was introduced in the CMSA, and highlights the obligations and responsibilities that are placed on licensed persons. These obligations are also important to financial institutions such as banks which carry out capital market activities who, as registered persons, are subject to certain fundamental investor protection provisions in the CMSA. This book will also be useful to anyone involved in capital raising exercises as it sets out how the law regulates specific corporate transactions, including takeovers. Corporate governance is especially relevant to public listed companies and this book explains how this imperative is translated into the law and the rules of the stock exchange. This area of law and regulation is extremely dynamic and the book provides some insight as to the trends in regulation and challenges which exist both on the domestic and international front.